Combining the Pulmonary Rehabilitation Decisional Score with the Bode Index and Clinical Opinion in Assigning Priority for Pulmonary Rehabilitation. (4th May 2018) - Olivares, Adriana; Vitacca, Michele; Comini, Laura
Abstract: Combining objective tools with clinical decision (CD) may help clinicians identify the priority for pulmonary rehabilitation (PR) in patients with COPD. We aimed to assess the specificity, sensitivity and efficiency of a new tool, the Pulmonary Rehabilitation Decisional Score (PRDS), and its correlation with the BODE index (BI) and CD in assigning PR priority. We retrospectively compared the three methods (CD vs. PRDS vs. BI) in 124 patients. We assigned low priority (LP), high priority (HP) and very high priority (VHP) to PR based on a priori scores of PRDS (LP = 0–10; HP = 11–17; VHP ≥18) and BI (LP = 0–2; HP = 3–5; VHP ≥6) and compared these with CD. PR priority assigned by the different methods was similar among groups, but did not often refer to the same subjects. PRDS and BI showed very high concordance with CD in defining VHP (97.8% and 95.6% for PRDS and BI, respectively), but were less concordant with CD in assigning LP and HP. Both PRDS and BI differently evaluated 38/124 cases compared to CD (PRDS underprescribed 18 and overprescribed 20; BI underprescribed 19 and overprescribed 19). However, a direct comparison between PRDS and BI showed that the discordance decreased to 8 underprescriptions and 10 overprescriptions (efficiency ∼85%). An objective instrument such as the PRDS can enhance CD with additional information on new aspects such as disability and fragility. PRDS and BI are nonetheless equally efficient at detecting discrepancies versus CD alone, especially when the priority for PR is defined as low or very high.